Guthlac Betwixt and Between: Literacy, Cross-Temporal Affiliation, and an Anglo-Saxon Anchorite - Weston, Lisa M. C. (Journal of medieval religious cultures, 2016)
Guthlac's saintly career saw his transformation from aristocratic warrior to monastic visionary. It saw him move physically from a warrior's secular hall to a monastic community and then to an anchorite's cell. Beyond this, however, even the ways later generations came to knowand perhaps be stimulated to emulateGuthlac move betwixt and between. That is, they involve repeated translations, movements between languages, between genres, between reading contexts. Felix's original Anglo-Latin vita must itself be triangulated among a variety of previous textual models. That Latin text was variously re-created as it was translated from Latin into multiple Old English texts. The Old English prose translations, vita and sermon, situate and invoke a significantly different Guthlac from that readable in the two (or perhaps three) extant devotional poems. Multiply liminal, Guthlacthe man and the textual memoryoffers his readers an exemplar through whom they engage in the reconstruction of monastic identity and literary subjectivity.